(3cJGH aj GdWHs
(3ChdgG (B:s
(3ajfJbT ai GdbhI GdYGbdI, jchf Hg eMdI YGdekG , hZGjJgG GdJejR Yf GdeTGQcGJ aj GdfhY hGdLfS HGdSYGOI GdCHOjI hdGTHjgI Ef HGdYbdG MGLI Edi WdH GdeQGJH GdehLHI GdceGd s
(3BNQgG (B:s
(3hEf bQHJ dg bQHGfkG ef MjhGfGJg UM aJM efM hgPG BNQ eG hLOfGg hGdMeO ddg QH GdYGdejf hUdi Ydi eMeO hBdg hUMHg CLeYjf s
(3GdcJGH oeQJH Ydi MQha GdoeYLes
(3aj CSeGA GdCOhjI hGdCeQGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B200 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs